Stepwise stress testing of different CAD-CAM lithium disilicate veneer application methods applied to lithium disilicate substructures - May, Jaren T.; Arata, Anelyse; Cook, Norman B.; Diefenderfer, Kim E.; Lima, Nelson B.; Borges, Alexandre L.S. [UNESP]; Feitosa, Sabrina (Elsevier, 2021)
Statement of problem: Whether a computer-aided design and computer-aided manufacture (CAD-CAM) fabricated high-translucency lithium disilicate veneer on a lithium disilicate substructure would increase the strength of the restoration compared with a traditional feldspathic porcelain veneer is unclear. Purpose: The purpose of this in vitro study was to evaluate the effect of different lithium disilicate veneer application methods on a lithium disilicate substructure on their biaxial flexural stress (BFS). Material and methods: Lithium disilicate disks were fabricated so that when combined with the veneering disks, they had a dimension of 12×1.2 mm. Experimental groups were as follows (n=15): resin-bonded lithium disilicate veneer, lithium disilicate veneer adhesively cemented to lithium disilicate; sintered lithium disilicate veneer, lithium disilicate veneer sintered to lithium disilicate; sintered feldspathic veneer, feldspathic porcelain applied to lithium disilicate; and monolithic lithium disilicate, the control group. Weibull distribution survival analysis was used to compare the differences in the resistance to fracture after fatigue. The total number of cycles was analyzed by using 1-way ANOVA (α=.05). A finite element analysis (FEA) was also performed. The maximum principal stress (MPS) was used as the failure criterion. Results: The sintered feldspathic veneer group had significantly lower fatigue resistance than sintered lithium disilicate veneer or resin-bonded lithium disilicate veneer (P<.05). The resin-bonded lithium disilicate veneer group showed significantly more fractured fragments than the other groups. No statistical difference was observed in the number of cycles. The lithium disilicate veneered groups presented similar resistance to fatigue as the monolithic specimens of the same overall dimensions. Higher peaks of MPS were observed for groups monolithic lithium disilicate, sintered lithium disilicate veneer, and sintered feldspathic veneer than for resin-bonded lithium disilicate veneer. Conclusions: Veneering a lithium disilicate substructure with a lithium disilicate veneer, bonded or sintered, increased resistance to fatigue compared with a feldspathic porcelain veneer. The lithium disilicate veneer groups had similar fatigue resistance to that of the monolithic group.